The Perfect Storm? Political Instability and Background Checks During COVID-19 - Anisin, Alexei (International Journal of Criminology and Sociology, 2023)
The COVID-19 pandemic has been observed to have increased aggressive behavior and violence in the United States. This study tests whether political instability events propelled gun purchasing behavior through a temporally sensitive analysis based on data drawn from the Armed Conflict Location & Event Data Project (ACLED) and monthly data from the FBI’s NICS National Instant Criminal Background Check System. It utilizes a multi-methodological framework featuring both regression modeling and qualitative comparative analysis. While results from statistical inquiry do not lend support to significant associations of any single variable on the outcome, the comparative configurational inquiry does identify three salient pathways that brought about background check increases during COVID-19. All three solutions feature the conditions of political instability and presidential election events. Alongside these factors, mass shooting occurrences are present in two of the identified solutions. These findings reveal that COVID-19 fostered a set of conditions and the formation of a “Perfect Storm” which resulted in the greatest number of annual gun purchases in recorded history.